A Symphony of Digital Public Service Innovation in Indonesia: Evidence from Indonesia Public Service Innovation Competition 2014-2022 - Pratama, M Rizki; Tualeka, Safarudin Hisyam; Prasetya, Arik (Jurnal Studi Pemerintahan, 2024)
Investigating digital public service innovation in Indonesia is essential for improving practical applications and developing a unified theoretical understanding of digital innovation in the public sector. This research is particularly relevant in the global conversation about digital progress in both developed and developing nations. Indonesia's situation is uniquely instructive for several reasons: At the macro level, despite ambitions to become a digital economy, Indonesia faces the challenge of low internet penetration. At the meso level, governmental goals to digitize public services are hindered by unclear integration strategies within bureaucratic systems, revealing a gap between policy and execution. At the micro level, the need for digital literacy in the public sector is evident, but Indonesian civil servants currently fall short of the required standards, highlighting an urgent need for skill development. This study is crucial not only for enhancing local practices but also for contributing to a broader understanding of digital transformation in the public sector across different stages of national development. The research methodically reviews and maps digital public service innovation within the Indonesian context, employing a best practices approach and using the PRISMA flowchart for content analysis. Data was sourced from the Kemenpan-RB database on the Public Service Innovation Competition (KIPP) from 2014-2022. This database is a primary source of information on Indonesian Public Service Innovation and is noted for its reliability. The findings reveal a diverse range of strategies that balance interactivity with information delivery, internal efficiency with external engagement, and collaboration with self-reliance, providing a comprehensive view of the current state and potential future of digital public service innovation in Indonesia.